Impact of switching to raltegravir and/or adding losartan in lymphoid tissue fibrosis and inflammation in people living with HIV. A randomized clinical trial. Issue 8 (20th July 2021) - Torres, B; Guardo, AC; Squarcia, M; Diaz, A; Fabra, A; Caballero, M; Ugarte, A; Leal, L; Gatell, JM; Plana, M; Garcia, F
Abstract : Background: Persistent inflammation and immune activation are associated with lymph node fibrosis and end‐organ diseases in treatment‐suppressed people living with HIV (PLWH). We investigated the effect of switching to raltegravir and/or adding losartan on lymphoid tissue fibrosis and on the inflammatory/immune‐activation mediators in treated HIV patients. Methods: Chronic HIV‐infected patients treated with two nucleoside reverse transcriptase inhibitors (2NRTI) and one non‐NRTI (NNRTI) or protease inhibitor (PI) during at least 48 weeks were randomized to four groups ( n  = 48): 2NRTI + efavirenz (EFV), 2NRTI + EFV + losartan, 2NRTI + raltegravir and 2NRTI + raltegravir + losartan for 48 weeks. Tonsillar biopsy and peripheral blood markers of CD4 and CD8 T‐lymphocyte activation and senescence, monocyte activation and soluble markers of inflammation were determined at baseline and at week 48 and compared between groups. Results: No changes in lymphoid tissue architecture were observed. Adding losartan had no impact on lymphocyte subsets. Conversely, patients who switched to raltegravir showed a higher decrease in all activated [CD4+CD38+HLA‐DR+, −0.3 vs . 0.48 ( P  = 0.033); CD8+CD38+ HLA‐DR+, −1.6 vs . 1.3 ( P  = 0.02)] and senescent [CD4+CD28–CD57+, −0.3 vs . 0.26 ( P  = 0.04); CD8+CD28–CD57+, −6.1 vs . 3.8 ( P  = 0.002)] T lymphocytes. In addition, the median CD4/CD8 ratio increased by 0.35 in patients in the raltegravir group vs . 0.03 in the other arms ( P  = 0.002). Differences between groups in monocyte subpopulations or soluble inflammation markers were not observed. Conclusions: Losartan had no effect on lymphoid fibrosis or immune activation/inflammation. Conversely, switching to a regimen with r altegravir significantly decreased activated and senescent T‐lymphocyte subpopulations and increased CD4/CD8 ratio in successfully treated PLWH.